Analisa Perpindahan Panas Konveksi Aliran di Atas Permukaan Berkas Pipa: Sebuah Kajian Literatur - Indra Mamad Gandidi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2013)
Heat transfer in flow across bank of tubes is of particular importance in the design of heat exchangers. Heat exchangers are found in numerous industrial applications, such as steam generation in a boiler or air cooling in the coil of an air conditioner. The Zakauskas’s correlation from the experimental data is more popular method that used to design of cross flow of heat exchanger. However, due to optimization process and more efficiency, several empirical equations were generated through the analytical and CFD methods. Hence, this paper was intended to perform a comprehensive study to analyze the heat transfer calculation of cross flow heat exchanger by using several methods in which it has been reported. Among of four methods are analyzed, the analytic method, normalization equations from CFD and Grimison’s correlation have good agreement to used for design of cross flow heat exchanger with the compact and non-compact configuration, while correlation of Zakauskas is only suitable for non-compact configuration.